Attenuation and dispersion of P-waves in porous rocks with planar fractures: Comparison of theory and numerical simulations - Lambert, Gracjan; Gurevich, Boris; Brajanovski, Miroslav (Society of Exploration Geophysicists, 2006)
To explore the validity and limitations of the theoretical model of wave propagation in porous rocks with periodic distribution of planar fractures, we perform numerical simulation using a poroelastic reflectivity algorithm. The numerical results are found to be in good agreement with the analytical model, not only for periodic fractures, but also for random distribution of constant thickness fractures.